Increased impact resistance of cross-country ski poles by improved, simulation assisted composite design - Granlund, M.; Gräsberg, G.; Zrida, H.; Fagerström, M.; Karlsson, A. (Proceedings, 2018)
High-end carbon fibre reinforced polymer (CFRP) ski poles of today are lighter and stiffer than previous generations, explained by the higher specific stiffness (stiffness to density ratio) for CFRPs, typically in the range of 0.1 GPa m3/kg compared to approximately 0.03 GPa m3/kg for aluminium. In this study, we have analysed different CFRP pole designs on the market by mechanical testing and microscopy. We conclude that the strive for optimised weight and bending stiffness has generally driven the pole design to be sub-optimal towards stiffness making them unnecessarily sensitive to transverse and impact loads. Based on the experimental findings, we have developed numerical simulation models to predict the bending and stress state in CFRP ski poles under axial as well as transverse (impact) loading conditions. These numerical model has then been used to find a new conceptual pole design with similar weight and stiffness but with seemingly higher impact resistance.